Microfinance for bankers and investors : understanding the opportunities and challenges of the market at the bottom of the pyramid - Rhyne, Elisabeth (New York : McGraw-Hill, 2009)
This book provides the facts and figures demonstrating the outstanding opportunities in this sector. Success stories from Citibank, Visa, Sequoia Capital, and other major companies.
Includes bibliographical references (p. 299-315) and index.
aug 02/05/13
Loans
Keywords: Microfinance; Investments; Banks and banking